Optimal Taxes on Wealth and Consumption in the Presence of Tax Evasion - Johann K. Brunner; Susanne Pech; Paul Eckerstorfer (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2010)
This article incorporates tax evasion into an optimum taxation framework with individuals differing in earning abilities and initial wealth. We find that despite the possibility of its evasion a tax on initial wealth should supplement the optimal nonlinear income tax, given a positive correlation between initial wealth and earning abilities. Further, even if income and initial wealth are taxed optimally, it is still desirable to levy a tax on commodities, though it can be evaded as well. Thus, our result provides a rationale for a comprehensive tax system. Optimal tax rates on commodities differ in general, however for the special case of a uniform evasion technology it turns out that equal rates are optimal if preferences are homothetic and weakly separable.
Keywords: D82; H21; H24; H26; 330; Optimal Taxation; Tax Evasion